A Ticking Clock? Preservation and Management of Greenland's Archaeological Heritage in the Twenty-First Century. (4th July 2018) - Harmsen, Hans; Hollesen, Jørgen; Madsen, Christian Koch; Albrechtsen, Bo; Myrup, Mikkel; Matthiesen, Henning
ABSTRACT: Evaluating the rate of deterioration at archaeological sites in the Arctic presents several challenges. In West Greenland, for example, increasing soil temperatures, perennial thaws, coastal erosion, storm surges, changing microbial communities, and pioneer plant species are observed as increasingly detrimental to the survival of organic archaeological deposits found scattered along the country's littoral zones and extensive inner fjord systems. This article discusses recent efforts by the REMAINS of Greenland project for developing a standardised protocol that defines the archaeological state of preservation, the preservation conditions, and asset value of organic deposits. Special emphasis is given to the degradation of materials such as bone and wood that are historically observed to be well-preserved in Greenland but now currently at risk. The protocol provides a baseline for monitoring future changes and will assist archaeologists in Greenland with a procedure for documenting and predicting areas of increasing vulnerability due to a warming climate.